Partitioning the Universe into gravitational basins using the cosmic velocity field. (25th July 2019) - Dupuy, Alexandra; Courtois, Helene M; Dupont, Florent; Denis, Florence; Graziani, Romain; Copin, Yannick; Pomarède, Daniel; Libeskind, Noam; Carlesi, Edoardo; Tully, Brent; Guinet, Daniel
ABSTRACT: This letter presents a new approach using the cosmic peculiar velocity field to characterize the morphology and size of large-scale structures in the local Universe. The algorithm developed uses the three-dimensional peculiar velocity field to compute flow lines, or streamlines. The local Universe is then partitioned into volumes corresponding to gravitational basins, also called watersheds, among the different end points of the velocity flow lines. This new methodology is first tested on numerical cosmological simulations, used as benchmark for the method, and then applied to the Cosmic-Flows project observational data in order to pay particular attention to the nearby superclusters including ours. More extensive tests on both simulated and observational data will be discussed in an accompanying paper.